ADHOC REMEDIES FOR MSMES PERFORMANCE IN NIGERIA: TECHNOLOGY INCUBATION PROGRAMME APPROACH - Kazeem, Kolawole R.; Olufemi, Olugbenga P.; Nofiu, Tunji N. (FUDMA Journal of Sciences, 2025)
Several efforts have been made in dealing with the violation of the assumptions made regarding the success story of MSMEs documented and some yielded results. Particular attention is that of the start-up problem. Business incubators are organizations created to help small and young firms become stable and profitable, which is a mainstay of economic development programs. The literature emphasizes several criteria and indicators to measure incubators’ performance or outcomes such as occupancy, jobs created, firms graduate, tenant revenues, number of patent applications per firm, number of discontinued businesses and others. Incubators have been observed as helping to build entrepreneurial cultures and clusters, acting as a catalyst for the development of integrated business support networks which include finance providers, universities, business schools, large companies, business professionals and government bodies. Due to the significance of technological innovation and entrepreneurship in shaping the future, this paper looks at technology incubation centres and their role in commercializing technologies and developing high value-added products, processes and services. In the new environment of rapid technological advances and globalizing trade, modern small businesses are playing a significant role in creating innovations, employment, income and growth with equity. This study deals with performance assessment of incubators with respect to job creation using the existing Technology Incubation Centres in Nigeria. The objectives of this paper will be focus on Technology Incubation Centres implementation processes, institutional structures and the services provided by the government to the incubatees and affiliates.
Keywords: Business Incubators; New Firms; Government Policy; Performance